Improved metagenomic analysis with Kraken 2 - Wood, Derrick E.; Lu, Jennifer; Langmead, Ben (Genome Biology, 2019)
Although Kraken’s k -mer-based approach provides a fast taxonomic classification of metagenomic sequence data, its large memory requirements can be limiting for some applications. Kraken 2 improves upon Kraken 1 by reducing memory usage by 85%, allowing greater amounts of reference genomic data to be used, while maintaining high accuracy and increasing speed fivefold. Kraken 2 also introduces a translated search mode, providing increased sensitivity in viral metagenomics analysis.